Heaven for everyone - Queen; Queen Music; EMI Music (United Kingdom : Queen Music, 1995)
Contains the single taken from the album Made In Heaven.
CD 1 : Heaven For Everyone (Single Version).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English